Mechanical and fracture characteristics of ultra-high performance concretes reinforced with hybridization of steel and glass fibers - Guler Fakhraddin Muhyaddin (Heliyon, 2023)
Ultra-high performance concrete (UHPC) provides exceptional mechanical and durability properties, but it is highly prone to cracking. Despite short steel fibers have been introduced to UHPC mixtures to mitigate brittleness and improve ductility, its effect on the tensile strength and fracture toughness becomes rather limited. This experimental study addresses hybridization of micro steel and glass fibers, and long hooked steel fibers to improve mechanical and fracture properties of ultra-high-performance concretes (UHPCs). Totally, 22 concrete mixtures were cast using mono and binary combinations of micro steel fiber (MSF), long hooked steel fiber (HSF) and micro glass fiber (GF) at 0, 0.25, 0.50, 0.75, 1.0, 1.5, and 2% by total fiber volume. The UHPCs were tested for compression, splitting, flexure, load-deflection diagram, fracture toughness, and characteristic length. Combined use of fibers suggested the performance order of MSF + HSF, MSF + GF, and HSF + GF on the effects tested. Using hooked steel fibers (HSF) in the hybrid blends seems remarkably promising as it has provided much higher ductility and discernible strain hardening. Using mono-GF did not improve ductility, even showed brittle failure.